SUMATRAN TIGER AND ITS HABITAT PROBLEMS AS THE IDEAS OF DIGITAL DRAWING ARTWORK - Azhar Natsir Ahdiyat (Balong International Journal of Design, 2020)
ABSTRACT The Sumatran Tiger is a tiger subspecies that is only found in Sumatra, Indonesia. This animal has exotic characteristics because of its unique stripes and body size, which is small among other living subspecies. Currently, Sumatran Tigers are categorized as critically endangered because there are only about 400-500 left in the wild. Habitats that are increasingly narrowing due to deforestation and habitat fragmentation as well as illegal hunting are real threats to these animals. This is an irony considering that the Sumatran Tiger is currently protected by the government through laws that are valid until now. Based on that, the writer has the idea to make digital drawing of Sumatran Tiger as the main theme of his artwork. This creation aims to answer the question about how to develop ideas, visualization, and visual-conceptual descriptions of Sumatran Tiger in the form of digital drawing. The drawing techniques used in this creation are outline, shading, block, and silhouette techniques using digital drawing software called Manga Studio EX. The creation of this work goes through three main steps, including preparation, execution process, and artwork presentation. In this creation, a digital drawing was produced in which visualization was made using visual elements and principles so that the idea had a correlation between the visual form and the concept of the Sumatran Tiger in relation to environmental problems (deforestation and habitat fragmentation).               Keywords: Sumatran Tiger, artwork, digital drawing.